ANALISIS FAKTOR TERHADAP SERVICE QUALITY ATRIBUT DAN PERANANNYA DALAM IMPLEMENTASI HARAPAN PENGUNA JASA PT KAI COMMUTER INDONESIA - Oktiani, Nurvi (www.bsi.ac.id, 2018)
Based on for increasing interest and needs in service sector, it should be for all of industries must provide encouragement for creating an appreciation in service quality procedure and provision, thereby for increasing service quality provider consist of land, port and air transportation management where is need a condition or procedure in service quality for fulfill expectation from customer or consumer. The research has been done with used quantitative research design method, with analytic technic data used factor analysis. Data has been got by spread of questionnaire to 400 samples with characteristic samples are customer whom use transportation by train or PT KAI Commuter line continuously with Jakarta, Bogor, Tangerang Bekasi and Depok Area. Samples have been taken by simple Random Sampling technic. Indicators or Characteristic for Service Quality Attributes consist of Intangibility, Inseparability and Unique dimensions, as for the Result of this research has been used Factor Analysis can be describe in Rotated Component Matrix divided two factors. From the result which two factors can be classified with Qualifying Factors and Vantage Factors, The Qualifying Factors consist of accuracy, trust, fulfill, fluctuation, expertise, and interaction, meanwhile Vantage Factors consist of Capability, Information, Performance, Active or Empathetic., From the result can be taken a decision or solution, It should be for service quality Provider in Commuter line must fulfill the Qualifying Factor and so that the standard of procedure or provision in service quality attributes can meet in standard of Expectation consumer demand